Cultural perspectives on services marketing - Laroche, Michel (Journal of services marketing, 2005)
This e-book features papers from the second meeting of the Royal Bank International Research Seminar which took place in Montreal at the John Molson School of Business, Concordia University, September 26 and 27, 2003. The main topic of this international seminar was Cultural perspectives on services marketing.